Manajemen Berbasis Sekolah dan Kesalahpahaman Persepsi - Soetam Rizky Wicaksono; Abdul Hakim; Kasmudin Mustapa (STKIP PGRI SITUBONDO, 2023)
While SBM (School-Based Management) has already been implemented in many countries, including Indonesia, the Education Council has already brought this idea to create a better education act. However, SBM still has the wrong paradigm among principals of schools in Indonesia. Some of them still hardly believe that SBM can leverage their school. This paradigm is based upon their narrow-minded point of view because many of them feel that there is no